2021
DOI: 10.12998/wjcc.v9.i15.3716
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid carcinoma of the pancreas — a rare tumor with an uncommon presentation and course: A case report and review of literature

Abstract: BACKGROUND Sarcomatoid carcinoma of the pancreas (SCP) is a rare type of pancreatic neoplasm, and only a few cases have been described in the literature. Histologically, it is composed mostly of atypical spindle cells with apparent sarcomatous features. CASE SUMMARY This is a report of a 61-year-old Chilean woman who underwent medical investigation for acute abdominal pain. Computed tomography identified a solid tumor in the tail of the pancreas with features suspicious… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Multivariate analysis showed that CDS was the only independent prognostic factor of both CSP and SCP, which indicating both diseases were surgical disease. This was in line with the findings that patients could achieved long-term survival after margin-negative surgery with or without adjuvant chemotherapy (22)(23)(24). However, further results from larger prospective studies are needed.…”
Section: Discussionsupporting
confidence: 88%
“…Multivariate analysis showed that CDS was the only independent prognostic factor of both CSP and SCP, which indicating both diseases were surgical disease. This was in line with the findings that patients could achieved long-term survival after margin-negative surgery with or without adjuvant chemotherapy (22)(23)(24). However, further results from larger prospective studies are needed.…”
Section: Discussionsupporting
confidence: 88%
“…Sarcomatoid carcinoma (SC) is relatively rare in clinical practice and can occur in multiple organs throughout the body, [6][7][8][9] but the lung and bladder are the most common sites. [10,11] HSC is an uncommon malignancy, accounting for 1.8% of all surgically resected liver malignancies and 3.9-9.4% of autopsy cases.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search on sarcomatoid carcinoma of the pancreas revealed 16 case reports from 1987 to 2021, only one of which briefly mentions that an FNA was performed prior to surgery and revealed "high-grade malignant epithelial cells." 11,12 In all cases, the histologic description included a combination of spindle cells, pleomorphic multinucleated giant cells, and adenocarcinoma, but none described any specific heterologous elements such as bone formation.…”
Section: Discussion/conclusionmentioning
confidence: 99%